y(y-3)+6=2y

Simple and best practice solution for y(y-3)+6=2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y(y-3)+6=2y equation:


Simplifying
y(y + -3) + 6 = 2y

Reorder the terms:
y(-3 + y) + 6 = 2y
(-3 * y + y * y) + 6 = 2y
(-3y + y2) + 6 = 2y

Reorder the terms:
6 + -3y + y2 = 2y

Solving
6 + -3y + y2 = 2y

Solving for variable 'y'.

Reorder the terms:
6 + -3y + -2y + y2 = 2y + -2y

Combine like terms: -3y + -2y = -5y
6 + -5y + y2 = 2y + -2y

Combine like terms: 2y + -2y = 0
6 + -5y + y2 = 0

Factor a trinomial.
(2 + -1y)(3 + -1y) = 0

Subproblem 1

Set the factor '(2 + -1y)' equal to zero and attempt to solve: Simplifying 2 + -1y = 0 Solving 2 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1y = 0 + -2 -1y = 0 + -2 Combine like terms: 0 + -2 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2

Subproblem 2

Set the factor '(3 + -1y)' equal to zero and attempt to solve: Simplifying 3 + -1y = 0 Solving 3 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 0 + -3 -1y = 0 + -3 Combine like terms: 0 + -3 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3

Solution

y = {2, 3}

See similar equations:

| G-9.3=9.2 | | 4y-2y+18=12 | | 5n-8n+4= | | 6+7n-49=-85 | | 20m+12=30m-18 | | -2p+6-8p+9= | | 9-5c=12-(6c-7) | | 9(x-3)=63 | | 4+6x-4=3x | | 8=-12+5n | | 3y(y-2)-2y(y-3)=4 | | 500=35-4x | | 4z+5=6z+7 | | -3[w+5]+5w=2[w-6] | | 8+5x=-27 | | -9f+2+8-5f= | | 6-s=18 | | [(2x+1)-5(x-4)]+4=10(x+3) | | 5h-(8+7h)= | | 2(4e)=40 | | 1=3(k+8) | | 5-7f+8f-3= | | 13=z+5 | | 6w+5=29 | | -9-1.1x=6.8 | | x+4x-21= | | (4x-23)+(2x+17)=180 | | -6x-2x+13=-11 | | 3[x+2]+2x=7[x-1]+9 | | 5+0.1Q=20-0.2Q | | 2(4e)=35 | | 2=11-20 |

Equations solver categories